Imagery Resource for the History of Physics in an Inclusive Room - Ana Santana Moreira; Isabela Moreira Reis; Lilian Amaral de Carvalho (Revista de Ensino de Ciências e Matemática, 2022)
The study of the History and Philosophy of Science allows a better understanding of the concepts and scientific evolution, contributing for the science in order to be perceived in a coherent way, displacing fragmented conceptions of knowledge or the belief in the absolute truth. This work aims to present a proposal for an imagery resource for the historical contextualization of Isaac Newton in an inclusive room, containing deaf and hearing students. The resource was produced by the selection of representative images on the topic under study and also contains support texts to help the teacher who intends to apply it. With the implementation of the proposal, it is intended to make the class more attractive for the deaf student, in addition to motivating all the students to understand the dynamic of scientific constructions. In addition, the proposal humanizes the teaching of Physics and contributes to the formation of critical and reflective citizens, whether deaf or hearing.